VARIASI PRAKTIK KONSUMSI HALAL: Studi Etnografi pada Masyarakat Minoritas Muslim di Bali dan Minahasa - Ali Amin; Ramli Semmawi (Jurnal Sosiologi Agama, 2022)
This paper investigates the practice of halal consumption among minority Muslim communities in Bali and North Sulawesi. Unlike many other parts of Indonesia, Bali and North Sulawesi have a dominant non-Muslim society along with their non-halal diet tradition. As many studies on minority groups have shown that being a minority group is prone to a cultural transformation. The author highlights how Muslims strategize their halal consumption practices in the setting of a dominantly non-Muslim and multicultural community. This study questions whether Muslims’ context as a minority influenced their behavior toward halal food (product) consumption. Which cultural factors have influenced Muslims’ practices of halal consumption in the setting of different cultures and societies? Using the ethnographic strategy in Bali and North Sulawesi the authors conclude two findings: First Muslim halal consumption is more influenced by the set of skills, habits, customs, and lifestyles called the cultural repertoire of each individual Muslim. Secondly, ideas, concepts, and moral norms (ideology) could also be very influential on Muslims’ behavior during a transitional time. This article also describes cultural repertoire, ideology, and transitional period which is influential to the Muslims’Inclusive and exclusive halal consumption practice.